Use of the HOPE score to assess survival outcome of hypothermic cardiac arrest selected by ECLS rewarming - Nicolas Hall; Jessika Métrailler-Mermoud; Valentin Rousson; Chloé Conforti; Amélie Dupasquier; Pierre-Nicolas Carron; Silke Grabherr; Bettina Schrag; Matthias Kirsch; Cheyenne Falat; Dominique Delay; Vincent Frochaux; et al. (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background We studied adult hypothermic cardiac arrest (CA) patients admitted to a University Hospital (UH) and a Regional Hospital (RH) for whom Extracorporeal Life Support (ECLS) was implemented. We used the HOPE score to estimate individual survival probabilities and to compare overall results between hospitals. Methods We included hypothermic CA patients who underwent ECLS between 2000 and 2022. We assessed the predicted survival probabilities by calculating the HOPE scores, both at individual and hospital levels. We assessed the performance of a HOPE score cutoff of 10% in predicting survival to hospital discharge, as ECLS rewarming is currently recommended when the HOPE is ≥ 10%. We also assessed the utility of the HOPE score in evaluating and comparing patient management within and between two hospitals. Results In the 46 patients with successful ECLS implementation, a HOPE score < 10% would have contraindicated and therefore prevented futile ECLS rewarming procedures for 17 patients (37%) who did not survive, while finding that ECLS was indicated for 100% of survivors. The observed survival rate was 24% (UH: 35%, RH: 11%) whereas the HOPE score predicted a survival rate of 35% (UH: 41%, RH: 26%), suggesting underperformance of ECLS rewarming among both hospitals. The difference of survival between the two hospitals was not statistically significant. Conclusions This study confirmed the utility of the HOPE score in estimating individual survival probabilities. The HOPE score may also be used to estimate the overall survival rate in a patient cohort, enabling internal quality-control and outcome results comparisons between different settings.